Manajemen Resiko Operasional Pada UMKM Pedagang Mie Ayam dan Bakso di Kecamatan Kramat - Putri, Salsa Ayu Kusuma; Amirah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a vital role in the economy, but their operations are not free from various risks that can hinder business continuity. This study aims to analyze operational risks and the implementation of risk management in MSMEs selling chicken noodles and meatballs in Kramat District. The research method used is a qualitative descriptive approach with a case study. Data collection techniques were carried out through direct observation, semi-structured interviews, questionnaires, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that MSMEs selling chicken noodles and meatballs face various operational risks, with the highest risks including hygiene issues, expired raw materials, damaged cooking utensils, rising raw material prices, and customer dissatisfaction due to service quality. Based on the level of risk, the very high risk category dominates with a percentage of 33%, indicating the need for priority handling. In mitigation efforts, MSMEs have implemented several strategies such as the FIFO system, routine equipment maintenance, hygiene control, and supplier management. However, external risk management is still not optimal. Therefore, this study concludes that operational risk management has been implemented by MSMEs selling chicken noodles and meatballs in Kramat District, but requires more structured improvement to maintain business stability and sustainability.